Transplantation of Insulin-Producing Cells Derived from Umbilical Cord Stromal Mesenchymal Stem Cells to Treat NOD Mice - Hwai-Shi Wang; Jia-Fwu Shyu; Wen-Sheng Shen; Hsin-Chi Hsu; Torng-Chien Chi; Chie-Pein Chen; Seng-Wong Huang; Yi-Ming Shyr; Kam-Tsun Tang; Tien-Hua Chen M.D. (Cell Transplantation, 2011)
Diabetes mellitus can be treated with islet transplantation, although there is a scarcity of donors. This study investigated whether human mesenchymal stem cells (MSCs) from umbilical cord stroma could be induced to differentiate into insulin-producing cells and the effects of retro-orbital injection of human insulin-producing cells for the treatment of nonobese diabetic (NOD) mice. MSCs were isolated from human umbilical cord stroma and induced to differentiate into insulin-producing cells using differentiation medium. Differentiated cells were evaluated by immunocytochemistry, RT-PCR, and real-time PCR. C-peptide release, both spontaneous and after glucose challenge, was measured by ELISA. Insulin-producing cells were then transplanted into NOD mice. Blood glucose levels and body weights were monitored weekly. Human nuclei and C-peptide were detected in mouse livers by immunohistochemistry. Pancreatic β-cell development-related genes were expressed in the differentiated insulin-producing cells. Differentiated cells' C-peptide release in vitro increased after glucose challenge. Further, in vivo glucose tolerance tests showed that blood sugar levels decreased after the cells' transplantation into NOD mice. After transplantation, insulin-producing cells containing human C-peptide and human nuclei were located in the liver. Thus, we demonstrated that differentiated insulin-producing cells from human umbilical cord stromal MSCs transplanted into NOD mice could alleviate hyperglycemia in diabetic mice.